The Effector Repertoire of the Hop Downy Mildew Pathogen Pseudoperonospora humuli - Purayannur, Savithri; Cano, Liliana M.; Bowman, Megan J.; Childs, Kevin L.; Gent, David H.; Quesada-Ocampo, Lina M. (Frontiers in Genetics, 2020)
Pseudoperonospora humuli is an obligate biotrophic oomycete that causes downy mildew, one of the most destructive diseases of cultivated hop that can lead to 100% crop loss in susceptible cultivars. We used the published genome of P. humuli to predict the secretome and effectorome and analyze the transcriptome variation among diverse isolates and during infection of hop leaves. Mining the predicted coding genes of the sequenced isolate OR502AA of P. humuli revealed a secretome of 1,250 genes. We identified 296 RXLR and RXLR-like effector-encoding genes in the secretome. Among the predicted RXLRs, there were several WY-motif-containing effectors that lacked canonical RXLR domains. Transcriptome analysis of sporangia from 12 different isolates collected from various hop cultivars revealed 754 secreted proteins and 201 RXLR effectors that show transcript evidence across all isolates with RPKM values > 0. RNA-seq analysis of OR502AA-infected hop leaf samples at different time points after infection revealed highly expressed effectors that may play a relevant role in pathogenicity. Quantitative RT-PCR analysis confirmed the differential expression of selected effectors. We identified a set of P. humuli core effectors that show transcript evidence in all tested isolates and elevated expression during infection. These effectors are ideal candidates for functional analysis and effector-assisted breeding to develop downy mildew resistant hop cultivars.